Síntese régio- e diastereosseletiva de oxazolidinonas via reação de cloroaminociclização promovidas por sais de Pd(II) - Papa, Bruna Lacerda [UNIFESP] (2018)
Allylic alcohol and especially its structural analogues are organic compounds of great interest to scientific community, since they can suffer a range of chemical transformations. Despite of several advances in reactions involving allylic alcohol derivatives using catalysis. It is possible to affirm that this is a fertile field to develop a variety of new symmetric and asymmetric reaction via metallic complexes as catalysts. A new methodology aiming the synthesis of oxazolidinones has been developed. Reactional time, temperature, Pd(II) source, quantity of CuCl2, solvent, catalyst loading and concentration were evaluated resulting in a optimize condition. The optimize reactional condition is: carbamate (0.2 mmol), PdCl2 (10 mol%), CuCl2 (1.0 mmol), LiCl (1.0 mmol) in ACN (0,10 mol.L-1) during 2,5 hours at 60 ˚C. The scope was explored where fourteen new oxazolidinones were obtain with yields from 50 to 95% and diastereoisomeric ratio up to 99:1. The developed methodology was efficient in a 15 times bigger scale (3.0 mmol) than the optimized one. Besides that, hydrogen NMR and computational studies helped us to propose a trans-catalytic-cycle to the formation of the majority diastereoisomer and a cis-catalytic-cycle to the minor diastereoisomer. In addition, four chemical transformations were done to obtain aminoalcohols, showing the synthetic versatility of the studied oxazolidinones.